Shallow seismic investigations and sediment sampling in the Weddell Sea amd Dronning Maud Land - Forsberg, Carl Fredrik; Austin, W E N; Häkkinen, Väinö Ami Juhani; Andersen, Espen Sletten (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; Weddellhavet; ekspedisjoner; marin geologi; sedimenter; seismologi

Timing of glacial events in Antarctica - diamond drilling into the glaciomarine sequence of the Weddell Sea continental shelf - Koç, Nalân; Kuvaas, Berit; Kristoffersen, Yngve; Hansen, Erik; Persson, Allan (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: NARE 1996/97; Sørishavet; Weddellhavet; glasiologi; kontinentalsokkel; sedimenter; sedimentologi; seismologi

Crustal development: Weddel Sea - Ross Sea region. Evolution of the Gondwana plate boundary in the Weddel Sea area - Kristoffersen, Yngve; Hinz, Karl (Geological evolution of Antarctica : proceedings of the Fifth International Symposium on Antarctic Earth Sciences, held at Robinson College, Cambridge, 23-28 August 1987, 1991)
Keywords: Antarktis; Weddellhavet; geofysikk; geologi; seismologi; tektonikk

The Crary Fan: A trough-mouth fan on the Weddell Sea continental margin, Antarctica - Kuvaas, Berit; Kristoffersen, Yngve (Marine Geology, 1991)
Multichannel seismic investigations show the presence of a large trough-mouth fan deposit on the continental margin in the southern Weddell Sea. A characteristic feature of the fan is relatively few, but large canyons and/or channels which appear to have been stable for long periods. Levees associated with the channels may reach thicknesses of more than 1 km. Drilling during ODP Leg 113 recorded the presence of glaciers in East Antarctica since early Oligocene time, and the seismic stratigraphic evidence suggests that the submarine fan is largely composed of glacigenic sediments. The channel-levee systems and complexes indicate several growth phases, apparently controlled by glacial/interglacial climate fluctuations, with maximum fan growth during glacial periods. The present interglacial period is characterized by strong and erosive flow of Ice Shelf Water running down the western slope of the fan and carrying only minor amounts of suspended matter. The fan is essentially sediment starved during interglacial periods. The dimensions of the channel-levee complexes and the persistent loci of sediment supply suggest that turbidite sedimentation resulted from melting of wet-based glaciers at or near the shelf edge, which has consequently prograded 70-80 km seaward.
Keywords: Sørishavet; Weddellhavet; havbunnen; isshelf; kontinentalmargin; kontinentalsokkel; marin geologi; seismologi

Iceberg scouring and sea bed morphology on the eastern Weddell Sea shelf, Antarctica - Lien, Reidar; Solheim, Anders; Elverhøi, Anders; Rokoengen, Kare (Polar Research, 1989)
Keywords: Antarktis; glasiologi; havbunnen; isberg; isshelf; kontinentalsokkel; morfologi; seismologi

Aeromagnetic reconnaissance over the Riiser-Larsen Ice Shelf, east Antarctica - Kristoffersen, Yngve; Aalerud, Jan (Polar Research, 1988)
Keywords: Antarktis; glasiologi; havbunnen; isbreer; isfront; seismologi

Seismic investigations in the Weddell Sea Embayment - Haugland, Kristen; Kristoffersen, Yngve; Velde, Anders (Tectonophysics, 1985)
Keywords: Antarktis; NARE 1976/77; NARE 1978/79; Weddellhavet; ekspedisjoner; seismologi

Seismic reconnaissance survey in the Weddell Sea - Haugland, Kristen (Antarctic geoscience, 1982)
Paper No. 46
Keywords: NARE 1976/77; Sørishavet; Weddellhavet; ekspedisjoner; havbunnen; sedimentologi; seismologi

The Continental Margin of Queen Maud Land/Antarctica: Seismic Sequences, Structural Elements and Geological Development - Hinz, Karl; Krause, W (Geologisches Jahrbuch. Reihe E, Geophysik, 1982)
Keywords: Dronning Maud Land; geologi; kontinentalmargin; seismologi

A microearthquake survey of Bouvet Island, South Atlantic - Kristoffersen, Yngve; Bungum, Hilmar (Tectonophysics, 1982)
A microearthquake survey carried out during the 1978–1979 Norwegian Antarctic Research Expedition indicates that only minor seismic activity is associated with the Bouvet volcano.
Keywords: Bouvetøya; NARE 1978/79; geofysikk; seismologi; vulkaner

The seismicity of the Bouvetøya region - Bungum, Hilmar; Kristoffersen, Yngve; Nilsen, Alf K. (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; seismologi; vulkaner

Prosessering av sonarbøyedata fra Antarktis - Hvidsten, Johannes (Universitetet i Bergen, Seismological Observatory, 1979)
Keywords: Antarktis; seismologi

Seismikk i Weddellhavet - Haugland, Kristen (Naturen, 1978)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Sørishavet; ekspedisjoner; havbunnen; sedimentologi; seismologi

Fra Sydpolen til "Utilgjengelighetens pol" (From The South Pole to The Pole of Inaccessibility) - Dybvadskog, Olav (Norsk Polarinstitutt. Årbok 1964, 1966)
Keywords: Antarktis; ekspedisjoner; forskning; glasiologi; gravimetri; meteorologi; observasjoner; seismologi

Annen etappe av Dronning Maud Land Traversen - Orheim, Olav (Norsk Polarinstitutt. Årbok 1965, 1965)
Keywords: Antarktis; Dronning Maud Land; ekspedisjoner; glasiologi; gravimetri; meteorologi; seismologi

General report of the expedition - Giæver, John; Schytt, Valter; Hisdal, Vidar (Geology, biology & general report of the expedition, 1963)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geologi; glasiologi; meteorologi; polarekspedisjoner; seismologi; topografi

Seismic shooting and related investigations - Robin, Gordon de Quetteville; Hisdal, Vidar (Glaciology III, 1958)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi; innlandsis; isbreer; morfologi; seismologi